Critical minerals: international approaches implementation in Ukraine - N. V. Bariatska (Мінеральні ресурси України)
The article discusses the definition of critical minerals (critical raw materials) and the main applications areas, including digital technologies, renewable energy and the defence industry. International approaches to criticality assessment are based on a range of indicators that determine the ratio of the economic value of a mineral to the risks of its supply. The degree of criticality of the same minerals may vary from country to country and region to region, depending on the development of the industry, import dependence and other factors. Approval of lists of critical minerals (critical raw materials) is a common practice in many countries around the world. An increasing number of countries have such lists and they tend to expand. An analysis of the critical minerals lists of the EU, USA, Canada, Australia, Japan, China and India showed that they have most of the same minerals (raw materials) considered critical, while there are also specific ones that are unique to a particular region. The article provides definitions of strategic and critical minerals in Ukraine, analyses their lists in terms of active special permits for subsoil use and their offers for auctions and production sharing agreements. The European Union is implementing a sustainable development strategy and taking steps to provide industry with critical raw materials, which includes the creation and development of reliable supply chains, recycling of raw materials, development of its own critical mineral resource base, and diversification of raw material supply sources. The European Commission has approved a list of 47 strategic operational projects for the extraction, enrichment, recycling and replacement of critical minerals. Given its geographical location and extensive mineral resource base, Ukraine can significantly improve the European Union's supply of critical minerals. In the context of the signing of a joint mining agreement with the United States and Ukraine's European integration, the introduction of international approaches to determining criticality, standardised terminology and approval of lists of critical minerals in Ukraine is extremely important.